2015
DOI: 10.1371/journal.pone.0140664
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Capacity of Plant Species to Accumulate Particulate Matter in Beijing, China

Abstract: Air pollution causes serious problems in spring in northern China; therefore, studying the ability of different plants to accumulate particulate matter (PM) at the beginning of the growing season may benefit urban planners in their attempts to control air pollution. This study evaluated deposits of PM on the leaves and in the wax layer of 35 species (11 shrubs, 24 trees) in Beijing, China. Differences in the accumulation of PM were observed between species. Cephalotaxus sinensis, Euonymus japonicus, Broussonet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 28 publications
9
75
0
4
Order By: Relevance
“…The loading of aerosols on leaf surfaces is generally between 20 and 100 μg cm À2 , although lower and higher values have been observed (Burkhardt 2010;Mo et al 2015;Popek et al 2013;Przybysz et al 2014;Sgrigna et al 2015). This is similar to the range of epicuticular waxes (35-100 μg cm…”
Section: Plant Adaptation To Foliar Accumulation Of Aerosolssupporting
confidence: 58%
See 3 more Smart Citations
“…The loading of aerosols on leaf surfaces is generally between 20 and 100 μg cm À2 , although lower and higher values have been observed (Burkhardt 2010;Mo et al 2015;Popek et al 2013;Przybysz et al 2014;Sgrigna et al 2015). This is similar to the range of epicuticular waxes (35-100 μg cm…”
Section: Plant Adaptation To Foliar Accumulation Of Aerosolssupporting
confidence: 58%
“…Studies with two-stage extraction of leaf surfaces with water followed by chloroform (Mo et al 2015;Popek et al 2013;Saebo et al 2012;Sgrigna et al 2015), and analysis of magnetic properties of leaves in high-aerosol urban environments (Hofman et al 2014), have shown that fine aerosols, including those with magnetic properties, become embedded in the surface waxes. This confirms earlier results with other techniques (Kozlov et al 2000;Lin and Schuepp 1996;Oliva and Raitio 2003;Oliva and Valdes 2004;Simmleit et al 1989).…”
Section: Wet and Occult Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, particles have led to hazy weather in many cities in China567. Thus, determining an effective way to reduce particle concentrations in urban areas has become a crucial endeavor.…”
mentioning
confidence: 99%